Anti-Arthritic Effect of Edaravone Against Complete Freund Adjuvant Induced Arthritis via Osteoclast Differentiation and HIF-1α–VEGF–ANG-1 Axis - Liu J; Zhao N; Su SH; Gao Y; Qi B (Dove Medical Press, 2023)
Jichao Liu,1 Nan Zhao,2 Shi-Han Su,3 Yun Gao,2 Bo Qi4 1Department of Hand and Foot Micro Burn Plastic Surgery, 3201 Hospital, Hanzhong, People's Republic of China; 2Department of Neurosurgery, The First Hospital of Kunming, Kunming, People's Republic of China; 3Department of Internal Medicine-Neurology, 920th Hospital of Joint Logistics Support Force, Kunming, People's Republic of China; 4Department of Orthopaedics, 920th Hospital of Joint Logistics Support Force, Kunming, People's Republic of ChinaCorrespondence: Bo Qi, Department of Orthopaedics, 920th Hospital of Joint Logistics Support Force, Kunming, 650000, People's Republic of China, Email kmqb66@sina.comBackground: Bone dysfunction is a crucial problem that occurs during rheumatoid arthritis (RA) disease. Osteoclast plays a significant role in bone resorption and osteoclast differentiation and its enhancement of bone destruction. Edaravone remarkably exhibited free radical scavenging and anti-inflammatory effects. The objective of the current investigation is to comfort the inhibitory effect of Edaravone (ED) against complete Freund adjuvant (CFA) rat model via inhibition of angiogenesis and inflammation.Methods: Subcutaneous injection of CFA (1%) was used to induce arthritis; the rats were divided into different groups and received the oral administration of ED. Paw edema, body weight, and arthritis score were regularly estimated. Biochemical parameters were estimated, respectively. We also estimate the level of hypoxia-inducible factor-1α (HIF-1α), angiopoietin 1 (ANG-1), and vascular endothelial growth factor (VEGF). We also checked into how ED affected the differentiation of osteoclasts utilising a co-culture system with monocytes and synovial fibroblasts in arthritis rats.Results: ED treatment significantly (P< 0.001) suppressed the arthritis score and paw edema and improved the body weight. ED treatment significantly (P< 0.001) altered the antioxidant parameters and pro-inflammatory cytokines: inflammatory mediator nuclear kappa B factor (NF-κB), cyclooxygenase-2 (COX-2), and prostaglandin E2 (PGE2), respectively. Furthermore, ED treatment significantly (P< 0.001) suppressed the level of ANG-1, HIF-1α, and VEGF, respectively. The results suggest that ED suppressed osteoclast differentiation and also decreased the level of cytokines and osteopontin (OPN), receptor activator for nuclear factor-κ B Ligand (RANKL) and macrophage colony stimulating factor (M-CSF) in the co-culture supernatant of monocytes and synovial fibroblasts.Conclusion: Edaravone could mitigate CFA via inhibiting angiogenesis and inflammatory reactions, which may be linked with the HIF-1α-VEGF-ANG-1 axis and also enhance the bone destruction of murine arthritis via suppression of osteoclast differentiation and inflammatory reaction.Keywords: Edaravone, oxidative stress, arthritis, inflammation, angiogenesis, osteoclast differentiation